Brown-Sequard Syndrome Caused By Cervical Disc Herniation: Case Report and Review - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
A herniated cervical disc is a very rare cause of Brown-Sequard syndrome. We report a 34-year-old man diagnosed as large C5 to C6 disc herniation producing acute Brown-Sequard Syndrome. This report details the importance of rehabilitation program to shorten the time returning to normal daily activity in addition to early diagnosis and surgery.
Keywords: Brown-sequard syndrome; cervical disc; rehabilitation